The Equus Datum and the Early Radiation of Equus in China - Sun, Boyang; Deng, Tao (Frontiers in Ecology and Evolution, 2019)
For comprehensive recognition on Equus Datum, we review all the stenonid species in China and discuss the phylogenetic relationship of early Equus. The conclusion indicates at least two dispersal waves of Equus into the Old World from North America, and the second wave led to a radiation of genus Equus in China. In China, the ages of the lower boundaries of the fossiliferous layers in classical Early Pleistocene faunal localities are all around 2.5 Ma (close to the age of lower boundary of the Quaternary) according to magnetostratigraphic and biostratigraphic analyses. All of the geochronological results reveal a status of China as an evolutionary center of Equus in Eurasia. In late Neogene, the dominant equid lineage in China was Hipparion. Even in Pliocene, when Hipparion was not as widespread as before, there were still 5 genera and 7 species. In Early Pleistocene, the genus Hipparion included only 2 genera and 3 species. In the meantime Equus dispersed into China depended on the connections of Bering land bridge (BLB) caused by lowered sea level under global cooling and Arctic ice-sheet forming. The rise of Equus was accompanied by the recession of Hipparion. The dispersal and radiation of Equus in China were not a coincidence, but a complicated process of adaption and competition, and a comprehensive outcome of significant climatic, tectonic and biotic events.